The prediction and estimation of gully erosion hazard as impact of climate change induced land degradation in Girei Basins Adamawa State, Nigeria - John W. Gundiri; Ibrahim E. Vahyala; Akwoga Atama; Kwari S. Joshua; Flavious B. Nkudu (The Proceedings of the Nigerian Academy of Science)
A two-year field study was conducted in Girei, Nigeria, to assess the influence of soil hydro-physical properties on gully erosion as a consequence of climate change across 41 locations. Gully channel parameters were measured at each site, and soil properties and erosion rates were analyzed using standard field and laboratory procedures. Results showed that the dominant soil type was sandy clay loam, with 60% sand, 22% silt, and 18% clay. The mean bulk density was 1.74 g/cm³, indicating high soil compactness, which promotes surface runoff and gully formation. The saturated hydraulic conductivity (Ksat) reached a maximum of 9.88×10⁻⁴ cm/s, suggesting rapid water movement through the soil profile. Key factors influencing soil loss exhibited both increasing and decreasing effects. Soil shear strength, hydraulic conductivity, porosity, and organic matter content reduced soil loss, whereas soil erodibility, surface runoff, clay content, gully head-cut, and altitude accelerated erosion. Site topography varied significantly, with altitudes of 274 m (Jabbilamba), 244 m (Girei River), 213 m (Damare), and 152 m (Labondo), where lower elevations corresponded with greater erosion severity. Statistical analysis indicated that runoff volume and altitude significantly influenced vertical and maximum soil loss (VSL & MSL), while porosity and gully head-cut were critical determinants of average soil loss (ASL). These findings highlight the importance of targeted soil conservation strategies, such as contour farming, vegetative cover, and erosion barriers, to mitigate gully expansion and soil degradation in the study area.